Youth sports in the heat: Recovery and scheduling considerations for tournament play - Bergeron, M. F. (Sports Medicine, 2009)
One of the biggest challenges facing numerous young athletes is attempting to perform safely and effectively in the heat. An even greater performance challenge and risk for incurring exertional heat injury is encountered when a young athlete has to compete multiple times on the same day, with only a short rest period between rounds of play, during a hot-weather tournament. Within the scope of the rules, tournament directors frequently provide athletes with only the minimum allowable time between same-day matches or games. Notably, prior same-day exercise has been shown to increase cardiovascular and thermal strain and perception of effort in subsequent activity bouts, and the extent of earlier exercise-heat exposure can affect performance and competition outcome. Incurred water and other nutrient deficits are often too great to offset during short recovery periods between competition bouts, and the athletes are sometimes 'forced' to compete again not sufficiently replenished. Providing longer rest periods between matches and games can significantly improve athlete safety and performance, by enhancing recovery and minimizing the 'carryover' effects from previous competition-related physical activity and heat exposure that can negatively affect performance and safety. Governing bodies of youth sports need to address this issue and provide more specific, appropriate and evidence-based guidelines for minimum rest periods between same-day contests for all levels of tournament play in the heat. Youth athletes are capable of tolerating the heat and performing reasonably well and safely in a range of hot environments if they prepare well, manage hydration sufficiently, and are provided the opportunity to recover adequately between contests.